IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DI DESA AER BALE KECAMATAN SOSA KABUPATEN PADANG LAWAS SUMATERA UTARA TAHUN 2023-2024 - Hasibuan, Ummu Salamah; Hadi, Sofyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research discusses the implementation of the Family Hope Program (PKH) in Aer Bale Village, Sosa District, Padang Lawas Regency, during 2023– 2024, and identifies the supporting and inhibiting factors in its implementation. PKH is a conditional social assistance program designed to improve the quality of human resources through access to education, health, and social welfare for low-income families. The background of this study is based on issues such as inaccurate data collection of beneficiaries, limited number of facilitators, and the presence of hard-to-reach areas. The study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation, involving informants from the village government, PKH facilitators, and beneficiary families (KPM). The results show that, in general, the implementation of PKH in Aer Bale Village has helped improve access to public services for low-income communities, although its effectiveness is still hampered by technical and administrative issues. Supporting factors include clear regulatory frameworks, active community participation, and cross-agency coordination. To enhance its effectiveness, improvements in the data collection system, an increase in the number of facilitators, and stronger coordination among relevant stakeholders are recommended. Keywords: Program Strategy, Establishing Program Standards, Developing Program SOP (Standard Operating Procedures), Program Output, Program Input.